2021
DOI: 10.1016/j.jfineco.2021.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Informed trading in government bond markets

Abstract: Using comprehensive regulatory data, we examine trading by different investor types in government bond markets. Our sample covers virtually all secondary market trading in gilts and contains detailed information on each transaction, including the identities of both counterparties. We find that hedge funds' daily trading positively forecasts gilt returns in the following one to five days, which is then fully reversed in the following month. A part of this short-term return predictability is due to hedge funds' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
(42 reference statements)
1
10
2
Order By: Relevance
“…The dashed lines denote 90% confidence intervals based on robust standard errors. (Color figure can be viewed at wileyonlinelibrary.com) analysis of Maggio et al (2019) and Czech et al (2021). For each client, we sort trading days into two groups-high connection days and low connection days-based on whether client's the number of connections in that day is above or below the average for the client.…”
Section: B1 Aggregate Connections and Portfolio Returnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dashed lines denote 90% confidence intervals based on robust standard errors. (Color figure can be viewed at wileyonlinelibrary.com) analysis of Maggio et al (2019) and Czech et al (2021). For each client, we sort trading days into two groups-high connection days and low connection days-based on whether client's the number of connections in that day is above or below the average for the client.…”
Section: B1 Aggregate Connections and Portfolio Returnsmentioning
confidence: 99%
“…It is important to highlight that our sorting of gilts using clients' orderflows is based on within-variation in connections as well, as opposed to only using characteristics that vary in the cross-section (e.g.,Czech et al (2021)). …”
mentioning
confidence: 99%
“…Price discovery in financial market is an important issue, especially in market microstructure research. Czech et al, (2021) state that price discovery is one of two main functions of financial markets, where the first function is to provide liquidity for all market participants and the second function is price discovery, which is a medium for creating prices of financial securities.…”
Section: Matrik: Jurnal Manajemen Strategi Bisnis Dan Kewirausahaanmentioning
confidence: 99%
“…Market microstructure literature defines various concepts of price discovery, including: "the process of finding the equilibrium price" (Czech et al, 2021), "collection and interpretation of news" (Banerjee & Pradhan, 2021), "the process of incorporating information implicit in investor trading into market prices" (Balcilar et al, 2021), "mechanisms for yield curve changes that are heterogeneous incorporation of private information and/or interpretation of public information through trading in the bond market" (Wang & Hu, 2021), and "integration of information in a timely manner into market prices" (Guidolin et al, 2021). From above definitions, it can be concluded that price discovery is a dynamic process that occurs naturally in which the process of creating market prices through rapid price adjustments driven by the presence of a series of information.…”
Section: Matrik: Jurnal Manajemen Strategi Bisnis Dan Kewirausahaanmentioning
confidence: 99%
See 1 more Smart Citation